Kindergarten Learners’ Mastery of English Dental Fricatives by Using Audiovisual Media in Bali Star Academy - Ni Kadek Arik Sintya Dewi; I Nyoman Udayana (e-Journal of Linguistics, 2020)
This research aims to 1) identify and describe the ability ofkindergarten learners in producing English dental fricatives and2) identify and describe the effect of audio-visual media forkindergarten learners’ ability in producing English dentalfricatives. This research used experimental approach with IntactGroup Comparison design. The subject of this research waskindergarten learners in Bali Star Academy. The data of thisresearch was collected through documentation method and wasanalyzed by using qualitative description. The result showed thatcontrol group had higher result compared to experiment groupduring the pre-test with 60.71% average score for the controlgroup and 17.71% average score for the experiment group. Afterthe audio-visual media applied for the experiment group, theresult changed into 76.28% average score for the experimentgroup and 67.85% for the control group.